Impact of Cataract Surgery on the Psychological State of the Elderly - Bárbara Nuria Suárez Rodríguez; Leonor Rosario Díaz Alfonso; Daniel Martínez Ojeda; Yutsimí Elia Fojaco Colina; Aleima Rodríguez Carvajal (Medisur)
Background: Progressively aging populations are one of the most distinctive demographic phenomena of the last decades. The elderly represent a particular risk group because typical characteristics of this stage of life, commonly associated with loss, are added to regular causes of psychopathologic disorders in today's social life. Objective: To assess the impact of cataract surgery on the psychological state of the elderly. Methods: A descriptive correlational study was conducted. The sample included 80 elder patients who attended the outpatient cataract pre-surgery consultation in the General University Hospital of Cienfuegos. They all presented some kind of affective disorder. The following psychosocial variables were analyzed: anxiety, depression, self-esteem and lifestyle. Sociodemographic variables such as age, sex, skin color, personal address, people they live with, education and occupation were also considered. Results: Predominant groups were those of females, white skinned, over 71 years old, average school level, married, living in urban residences and within a multigenerational household. Depression levels were high (30 %) before surgery. After surgery they decreased in a 5 %. High levels of anxiety also decreased from 53 % to 10 %. Inadequate self-esteem before surgery (65 %) decreased to 20 % after surgery. Conclusions: Cataract surgery has a favorable effect on the psychological status of the elderly.